The design of development - Tinbergen, Jan.; The Economic Development Institute, International Bank for Reconstruction and Development (Baltimore : The Johns Hopkins Press, 1958)
This is a study prepared in 1955 for the World Bank and has been the basis for discussions of development policies and problems of programming and project appraisal. It includes topics like: elements of development policy; the essence of programming; appraisal of projects: public investment among others.
Includes index.
lje 18/09/2018
Loans
Keywords: Economic development